ДИДАКТИКА гуманитарных дисциплин при создании АДАПТИВНОЙ МОДЕЛИ КОМПЬЮТЕРНОГО ОБУЧЕНИЯ ДЛЯ СТУДЕНТОВ ВУЗОВ ТЕХНИЧЕСКОГО НАПРАВЛЕНИЯ - Хажиева, И.А. (SCIENCE and SOCIETY, 2022)
This article is focused on the didactics of the humanities when creating an adaptive model of computer learning, as well as the possibilities of improving the quality of education through the individualization of education.